The spatio-temporal distribution patterns of biting midges of the genus Culicoides in Salta province, Argentina - Veggiani Aybar, Cecilia Adriana (2012)
The goal of this survey was to analyze the spatio-temporal distribution patterns of Culicoides Latreille species (Diptera: Ceratopogonidae) and their relationship with environmental variables in Salta, northwestern Argentina. Culicoides were collected monthly from January 2003 through December 2005. The influence of the climatic variables on population abundance was analyzed with a multilevel Poisson regression. A total of 918 specimens belonging to five species were collected. The most abundant species was Culicoides paraensis Goeldi (65.5%), followed by Culicoides lahillei Iches (14.6%) and Culicoides debilipalpis Lutz (7.6%). The highest seasonal abundance for C. paraensis, C. debilipalpis and C. lahillei occurred during the spring and summer. A Poisson regression analysis showed that the mean maximum and minimum temperature and the mean maximum and minimum humidity were the variables with the greatest influence on the population abundance of Culicoides species.